1991
DOI: 10.1084/jem.173.2.423
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies against the multicatalytic proteinase in patients with systemic lupus erythematosus.

Abstract: Sera from patients with systemic lupus erythematosus contain specific autoantibodies directed against different polypeptide components of the multicatalytic proteinase (also known as proteasome or prosome). These human autoantibodies, in contrast to polyclonal antibodies obtained in rabbits against the purified enzyme, recognize highly conserved epitopes of the multicatalytic proteinase polypeptides from yeast to human.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…After electrophoresis the gels were either stained with Coomassive blue or transferred to nitrocellulose as de scribed [7], Nitrocellulose filters were reversibly stained with 0.1 % Ponceau red in 1 % acetic acid and blocked overnight at 4°C with blocking buffer: 50 mmol/l Tris-Cl (pH 7.5), 0.5 mol/1 NaCl and 3% (w/ v) bovine serum albumin (BSA) for immunoblot analy sis. The filters for immunoblot were incubated with anti-C2 antibody affinity-purified against: the fulllength recombinant C2 polypeptide; the C2 protein construct mC2.26 selecting antibodies directed against the C2 COOH (DEPAEKADEPMEH), or the con struct mC2.24 for antibodies directed to a different epitope of the C2 subunit located in the N-terminal in respect to the C2 COOH as described [8], Immunoblot developing was done either by the chemiluminescence method (ECL, Amersham) or with 4-chloro-l-naphthol.…”
Section: Protein Analysis By Sds-page and Immunoblottingmentioning
confidence: 99%
See 1 more Smart Citation
“…After electrophoresis the gels were either stained with Coomassive blue or transferred to nitrocellulose as de scribed [7], Nitrocellulose filters were reversibly stained with 0.1 % Ponceau red in 1 % acetic acid and blocked overnight at 4°C with blocking buffer: 50 mmol/l Tris-Cl (pH 7.5), 0.5 mol/1 NaCl and 3% (w/ v) bovine serum albumin (BSA) for immunoblot analy sis. The filters for immunoblot were incubated with anti-C2 antibody affinity-purified against: the fulllength recombinant C2 polypeptide; the C2 protein construct mC2.26 selecting antibodies directed against the C2 COOH (DEPAEKADEPMEH), or the con struct mC2.24 for antibodies directed to a different epitope of the C2 subunit located in the N-terminal in respect to the C2 COOH as described [8], Immunoblot developing was done either by the chemiluminescence method (ECL, Amersham) or with 4-chloro-l-naphthol.…”
Section: Protein Analysis By Sds-page and Immunoblottingmentioning
confidence: 99%
“…After the cells had grown to 50-70% confluency, the coverslips were fixed and permeabilized with absolute methanol at -20 ° C for 15 min, rinsed 3 times with TBS (50 mmol Tris-Cl, pH 7.5; 0.15 mol/1 NaCl) and used for indirect immunofluorescence. Anti-MCP antibody [7] was added at a 1/400 dilution in TBS con taining 3% BSA and incubated with the cells for 1 h at room temperature. After three washes (10 min each) with TBS, the second antibody, a fluorescein-conju gated goat anti-rabbit antibody (Boehringer), was add ed at a 1/300 dilution in TBS containing 3% BSA, together with 2 gmol/1 of 4,6-diamidino-2-phenylindole) for DNA staining.…”
Section: Cell Immunofluorescencementioning
confidence: 99%
“…We have also detected a gene coding for the proteasome a7/C8 subunit protein on the protein filters and have confirmed its specificity on protein microarrays and by Western immunoblotting analysis. In humans, proteins of the 20S proteasome, such as the subunit C9a, have been frequently recognized in different autoimmune diseases, including SLE [25,26], suggesting these proteins may have potential as marker proteins for general autoimmune inflammation and cell damage [27]. In this context, we do not know if the proteasome a7/C8 subunit is specific for SLE or is detected in a more general way, in other mouse models of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 91%
“…Originally, 35% of studied SLE patients were shown to have antiproteasome antibodies [210]. A more recent report has shown that 58% of patients with SLE and 62% of patients with myositis have antiproteasome antibodies which were not detected in healthy control individuals or in patients with mixed connective tissue disease and rheumatoid arthritis.…”
Section: Various Immunological Disordersmentioning
confidence: 98%